(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Chemical pesticides, which are employed in agricultural fields to limit the damage caused by pests and diseases, represent several long-term dangers and threats to living things. Biopesticides are currently used in a variety of agricultural and horticultural settings, including organic farming, integrated pest management systems, and conventional farming. Despite their potential benefits, there are several barriers to the widespread adoption of biopesticides. In this review, we will focus on the current challenges and future prospects of the use of chemical pesticide in pest management.